1995
DOI: 10.1111/j.1365-2125.1995.tb05778.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics in lactating women: prediction of alprazolam transfer into milk.

Abstract: 1 Alprazolam, a triazolobenzodiazepine, is extensively prescribed for the treatment of anxiety disorders, which predominantly affect women of child-bearing age. The purpose of the present study was to assess the pharmacokinetics of alprazolam and its two hydroxylated metabolites: 4-hydroxy-alprazolam and a-hydroxy-alprazolam in lactating human volunteers and to test the predictability of four recently reported models for drug transfer into milk based on physicochemical properties. 2 Multiple milk and serum sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 28 publications
1
23
0
2
Order By: Relevance
“…Cette éva-luation devant reposer sur des informations scientifiques validées et actualisées, il est donc indispensable de savoir doser les médicaments dans le lait, en particulier ceux pouvant poser problème chez le nouveau-né ou le nourrisson allaité, comme c'est le cas des benzodiazépines et des psychotropes en général. Concernant les techniques HPLC publiées [24,63], le principe évoqué par les auteurs a été similaire au nôtre : valider une méthode analytique déjà utilisée en routine pour les échan-tillons plasmatiques. Une des deux techniques publiées [24] présente une LOQ semblable à la nôtre (diazépam 50 ng/mL).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Cette éva-luation devant reposer sur des informations scientifiques validées et actualisées, il est donc indispensable de savoir doser les médicaments dans le lait, en particulier ceux pouvant poser problème chez le nouveau-né ou le nourrisson allaité, comme c'est le cas des benzodiazépines et des psychotropes en général. Concernant les techniques HPLC publiées [24,63], le principe évoqué par les auteurs a été similaire au nôtre : valider une méthode analytique déjà utilisée en routine pour les échan-tillons plasmatiques. Une des deux techniques publiées [24] présente une LOQ semblable à la nôtre (diazépam 50 ng/mL).…”
Section: Discussionunclassified
“…Une des deux techniques publiées [24] présente une LOQ semblable à la nôtre (diazépam 50 ng/mL). Pour la seconde technique [63], elle concerne l'alprazolam, molécule à demi-vie courte et donc théoriquement sans inté-rêt pour le suivi thérapeutique des nourrissons.…”
Section: Discussionunclassified
“…It was observed that the milk levels of alprazolam were in close agreement with that of serum with the mean milk to serum ratio (M/S ratio) of 0.36 ± 0.11. The mean residence time of alprazolam in milk was 18.93 ± 7.03 h, which is very close to that of serum, 16.42 ± 4.69 h (Oo et al ., ).…”
Section: Breast Milkmentioning
confidence: 97%
“…Oo et al . () developed and validated a HPLC‐UV method for the determination of alprazolam in human milk. To 2 mL of milk 5 mL of acetonitrile was added to precipitate proteins.…”
Section: Breast Milkmentioning
confidence: 98%
See 1 more Smart Citation